Ergonomics Demonstration as an Effort to Low Back Pain Preventive Behavior in Apple Chip Making Workers at Bumiaji Village, Batu City - Anis Fitrianingsih; Ukik Agustina (Universitas STRADA Indonesia, 2025)
Low Back Pain is pain that is felt in the lower back area starting from below the ribs or waist radicular pain is localized and both are often accompanied by pain from the legs to the legs. Actions to improve low back pain prevention behavior by providing ergonomics demonstration. The purpose of the study was to determine the effect of ergonomics demonstration on low back pain prevention behavior in apple chip making workers in Bumiaji Village, Batu City. The research design uses a Pre-Experiment design with a One-Group Pre-Post Test Design. The research population was 240 apple chip making workers and the research sample was 71 respondents with determination using simple random sampling. The data collection technique uses an instrument in the form of an observation sheet for low back pain prevention behavior. The data analysis method used is the Paired T Test. The results of the study showed that before being given the ergonomics demonstration, almost all 57 (80.3%) respondents had low back pain prevention behaviors in the poor category and after being given the ergonomics demonstration, almost all 58 (81.7%) respondents had low back pain prevention behaviors in the good category. The results of the Paired T Test proved that there was an effect of ergonomics demonstration on low back pain prevention behavior in apple chip makers in Bumiaji Village, Batu City, with a value of p = (0.000). The conclusion Ha is accepted, meaning that there is an effect of ergonomics demonstration on low back pain prevention behavior in apple chip making workers in Bumiaji Village, Batu City, meaning that ergonomics demonstration given for 20-30 minutes for 1 treatment is able to improve low back pain prevention behavior from less to good.